Organizational Culture and Work Environment in an Effort to Improve the Performance of Cirebon Regency Environmental Agency Employees Im - Tiara Sandra; Noveria Susijawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Employee performance is an important factor in determining the success of an organization, especially in government agencies that provide public services. This study aims to analyze the influence of organizational culture and work environment on employee performance at the Cirebon Regency Environmental Office. This study uses a quantitative approach with a survey method involving 134 respondents from a population of 200 employees determined using the Slovin formula. Data were collected through questionnaires using the Likert scale and analyzed using SPSS through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and determination coefficients. The results of the study show that organizational culture and work environment partially and simultaneously have a positive and significant effect on employee performance. The determination coefficient shows that both variables explain some of the variation in employee performance, while the rest is influenced by other factors outside of the research model. These findings emphasize the importance of strengthening organizational culture and creating a supportive work environment to improve employee performance.